Development and Validation of a Methodology to Measure Exhaled Carbon Dioxide (CO2) and Control Indoor Air Renewal - Marta Baselga; Juan J. Alba; Alberto J. Schuhmacher (COVID, 2023)
The measurement of carbon dioxide (CO2) has emerged as a cost-effective and straightforward technique for indirectly managing indoor air quality, aiding in the reduction of the potentially pathogen-laden aerosol concentrations to which we are exposed. Unfortunately, inadequate practices often limit the interpretation of CO2 levels and neglect methodologies that ensure proper air renewal. This study presents a novel methodology for measuring and controlling indoor CO2 levels in shared spaces, comprising four stages: analysis, diagnosis, correction protocols, and monitoring/control/surveillance (MCS). This methodology underwent validation in practical settings, including a cultural center (representing spaces with uniform activities) and 40 commercial spaces (with diverse activities) in Zaragoza, Spain. The results indicate the feasibility of swiftly implementing measures to enhance shared air renewal, with the immediate opening of doors and windows being the most direct solution. The proposed methodology is practical and has the potential to mitigate the risk of the aerosol transmission of respiratory diseases. Consequently, we anticipate that this work will contribute to establishing methodological foundations for CO2 measurement as a valuable, standardized, and reliable tool.